2021
DOI: 10.1101/2021.12.22.473803
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Taking stock of the past: A psychometric evaluation of the Autobiographical Interview

Abstract: Autobiographical memory (AM) involves a rich phenomenological re-experiencing of a spatio-temporal event from the past, which is challenging to objectively quantify. The Autobiographical Interview (AI; Levine et al., 2002, Psychology & Aging) is a manualized performance-based assessment designed to quantify episodic (internal) and semantic (external) features of recalled and verbally conveyed prior experiences. The AI has been widely adopted yet has not undergone a comprehensive psychometric validation. We… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 214 publications
1
12
0
Order By: Relevance
“…We investigated age differences in AM, hippocampus and temporal pole volumes, and AM‐volume associations in a large sample of healthy younger and older adults, using the Autobiographical Interview (Levine et al, 2002; Lockrow et al, 2021) to quantify the episodicity of AM recollection. Consistent with predictions, younger adult recollections were more episodic with a higher density of episodic (internal) than semantic (external) details.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We investigated age differences in AM, hippocampus and temporal pole volumes, and AM‐volume associations in a large sample of healthy younger and older adults, using the Autobiographical Interview (Levine et al, 2002; Lockrow et al, 2021) to quantify the episodicity of AM recollection. Consistent with predictions, younger adult recollections were more episodic with a higher density of episodic (internal) than semantic (external) details.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using the AI typically report detail counts, whereas here we report on detail density, a metric that controls for the overall verbal output of recollections. We have previously introduced density scores as a novel dependent variable from the AI (Spreng et al, 2018), and have recently found that they are more sensitive to age effects than detail counts, and provide more reliable and valid estimates of individual differences in AM (Lockrow et al, 2021). In controlling for verbosity, density scores measure the amount of all verbal output dedicated to conveying episodic or semantic details about a personal past event.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations